Metal clad laminate and printed wiring board

JP7644611B2Active Publication Date: 2025-03-12ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021016709
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-04
Publication Date
2025-03-12
Estimated Expiration
2041-02-04

AI Technical Summary

Benefits of technology

【0008】 本発明の一態様によれば、樹脂硬化物と金属層との密着性に優れ、更に電気特性に優れる金属張積層体及びこれを含むプリント配線板が提供され得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644611000022
    Figure 0007644611000022
  • Figure 0007644611000001
    Figure 0007644611000001
  • Figure 0007644611000002
    Figure 0007644611000002
Patent Text Reader

Abstract

To provide a metal-clad laminate excellent in adhesion between a resin cured product and a metal layer and electrical properties, and a printed wiring board including the same.SOLUTION: A metal-clad laminate includes a resin cured product and a metal layer laminated to contact the resin cured product. The resin cured product including a structure region derived from a compound including a polymerizable group and a heteroaromatic ring having one or more nitrogen atoms has a relative dielectric constant of 3.3 or less and a dielectric dissipation factor of 0.003 or less, and the surface ten-point average roughness Rzjis of the metal layer contacting the resin cured product is 2.0 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal clad laminate and a printed wiring board. [Background technology]

[0002] In recent years, with the advancement of information network technology and the expansion of services utilizing information networks, electronic devices are required to have a larger capacity of information and a faster processing speed. In order to meet these demands, materials for substrates such as printed wiring boards are required to have low dielectric constants and low dielectric loss tangents in addition to the conventional properties such as heat resistance, flame retardancy, and peel strength with metal foil. For this reason, further improvements in resin compositions used for substrates such as printed wiring boards are being considered. In particular, printed wiring boards for high-frequency transmission applications must have a high degree of compatibility between the above properties in order to maintain high processing speeds.

[0003] Patent Document 1 describes a curable resin composition that contains an epoxy compound (A), a triazole compound (B), and a tertiary amine compound (C) having a specific structure, as a resin composition that enables the formation of a cured product that has excellent adhesion to a conductor layer in a multilayer printed wiring board. Furthermore, Patent Document 2 describes a curable resin film used for multilayer printed wiring boards, which has high adhesion to conductors and excellent electrical properties, and which has at least two layers: (a) a layer formed from a resin composition containing a polyphenylene ether resin and triallyl isocyanurate and / or triallyl cyanurate, and (b) a layer formed from a compound or polymer compound having a glass transition temperature of 200°C or lower and containing at least one atom selected from oxygen atoms, nitrogen atoms, and sulfur atoms and an aromatic ring, and at least one outermost layer of the film is formed from the above layer (b). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2016 / 088358 [Patent Document 2] JP 2001-298275 A Summary of the Invention [Problem to be solved by the invention]

[0005] The curable resin compositions and curable resin films described in Patent Documents 1 and 2 aim to obtain good electrical properties of a metal-clad laminate by improving the adhesion between the cured resin and the conductor, but the electrical properties are still not sufficient even with the techniques described in the above documents. In particular, to achieve good high-frequency properties (i.e., low transmission loss), it is necessary to reduce the skin resistance of the conductor, but the techniques described in the above documents have high skin resistance, and although the adhesion between the cured resin and the conductor may be good to a certain extent, there is still room for improvement in the electrical properties.

[0006] The present invention has an object to solve the above problems and to provide a metal clad laminate having excellent adhesion between a cured resin and a metal layer and further excellent electrical properties, and a printed wiring board including the same. [Means for solving the problem]

[0007] The present disclosure includes the following aspects. [1] A metal clad laminate comprising a cured resin and a metal layer laminated in contact with the cured resin, the cured resin contains a structural portion derived from a compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms, the cured resin has a relative dielectric constant of 3.3 or less and a dielectric tangent of 0.003 or less, The ten-point average roughness R of the surface of the metal layer that comes into contact with the cured resin zjis The metal clad laminate has a thickness of 2.0 μm or less. [2] The element average length R of at least one surface of the metal layer sm The metal clad laminate according to embodiment 1, wherein the thickness is 5.0 μm or more. [3] The metal clad laminate according to the above-mentioned embodiment 1 or 2, wherein the static friction coefficient of the surface of the metal layer that comes into contact with the cured resin is 0.38 μs or more and 0.50 μs or less. [4] The element average length R of at least one surface of the metal layer sm The metal clad laminate according to any one of the above embodiments 1 to 3, wherein the thickness is 5.0 μm or more and 100.0 μm or less. [5] The metal clad laminate according to any one of the above embodiments 1 to 4, wherein the compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms has a 1,2,4-triazole structure or a tetrazole structure. [6] A compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms, represented by the following general formula (1): [ka] {where, R 1 represents a hydrogen atom or a monovalent hydrocarbon group, R 2 is a hydrogen atom, a methyl group, or an ethyl group, and X is represented by the following general formula (X-1): [ka] (In the formula, R 3 is a hydrogen atom or a monovalent hydrocarbon group.) or the following formula (X-2): [ka] or the following general formula (X-3): [ka] (In the formula, R 4 is a hydrogen atom or a monovalent hydrocarbon group; and Y is a sulfur atom or an NH group. The metal clad laminate according to embodiment 5, wherein the compound is a compound represented by the formula: [7] The metal clad laminate according to any one of the above embodiments 1 to 6, wherein the cured resin has a crosslinked structure formed by crosslinking polyphenylene ether having two or more terminal curable functional groups. [8] The metal clad laminate according to embodiment 7, wherein the cured resin further has a crosslinked structure formed by crosslinking with a crosslinking agent. [9] The cured resin contains a structural portion derived from an elastomer, The elastomer is at least one selected from the group consisting of a block copolymer of a vinyl aromatic compound and an olefin-based alkene compound, a hydrogenated product thereof, and a homopolymer of a vinyl aromatic compound; and The metal clad laminate according to any one of the above-mentioned embodiments 1 to 8, wherein the content of the unit derived from the vinyl aromatic compound in the block copolymer or the hydrogenated product thereof is 20% by mass or more.

[10] The metal clad laminate according to any one of the above embodiments 1 to 9, further comprising a glass cloth.

[11] A printed wiring board comprising the metal clad laminate according to any one of the above embodiments 1 to 10. Effect of the Invention

[0008] According to one aspect of the present invention, it is possible to provide a metal clad laminate having excellent adhesion between a cured resin and a metal layer and further excellent electrical properties, and a printed wiring board including the same. [Brief description of the drawings]

[0009] [Figure 1] 1 is a 1H-NMR chart of a heterocyclic compound according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, a mode for carrying out the present invention (hereinafter also simply referred to as "the present embodiment") will be described, but the present invention is not limited to the following embodiment. Therefore, the following embodiment can be appropriately modified and carried out within the scope of the gist of the present invention. Unless otherwise specified, the various characteristics referred to in the present embodiment are values ​​measured by the method described in the [Example] section of this disclosure or a method that is understood to be equivalent to the method by a person skilled in the art.

[0011] ≪Metal-clad laminate≫ One aspect of the present invention provides a metal clad laminate including a cured resin and a metal layer laminated in contact with the cured resin. In one aspect, the cured resin includes a structural portion derived from a compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms. In one aspect, the cured resin has a relative dielectric constant of 3.3 or less and a dielectric loss tangent of 0.003 or less. In one aspect, the ten-point average roughness R of the surface of the metal layer in contact with the cured resin is 0.003 or less. zjis is less than 2.0 μm.

[0012] In order to laminate a metal layer to a cured resin with good adhesion in a metal clad laminate, it is advantageous for the metal layer to have a certain degree of roughness, but such a highly rough surface leads to an increase in the skin resistance of the metal layer, and therefore to a decrease in the electrical properties of the metal clad laminate. The present inventors have unexpectedly found that by combining a cured resin having a specific structural portion and specific dielectric properties with a metal layer having a specific surface roughness, a metal clad laminate can be obtained in which the adhesion between the metal layer and the cured resin is good despite the metal layer having a low surface roughness, and which exhibits good electrical properties. Each element of the metal clad laminate will be described below.

[0013] <Metal layer> In the metal clad laminate of this embodiment, the metal layer is laminated in contact with the cured resin. Examples of the metal layer include aluminum foil and copper foil, and copper foil is preferred because of its low electrical resistance. The skin resistance of the metal layer is one of the main causes of the deterioration of the electrical properties of the metal clad laminate. In particular, in high-frequency transmission applications (for example, applications such as printed wiring boards for high-frequency transmission), the skin resistance has a large effect on performance, so it is desirable to reduce it as much as possible. When the surface of the metal layer is smooth, the skin resistance is generally reduced while the adhesion to the cured resin is also reduced. In the metal clad laminate of this embodiment, the cured resin has a structural portion derived from a compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms, and therefore exhibits unexpectedly good adhesion even to a metal layer having a smooth surface.

[0014] The ten-point average roughness R of the metal layer surface that comes into contact with the cured resin zjis From the viewpoint of reducing the skin resistance, in one embodiment, the surface roughness R is 2.0 μm or less, or 1.4 μm or less, or 1.2 μm or less, or 0.9 μm or less. The cured resin may be laminated on one or both sides of the metal layer. zjis From the viewpoint of further improving the adhesion between the cured resin and the metal layer, the roughness may be, for example, 0.02 μm or more, or 0.05 μm or more, or 0.10 μm or more. In the present disclosure, the ten-point average roughness is the sum of the average of the heights of the top five peaks in ascending order from the highest peak and the average of the depths of the top five valleys in descending order from the deepest valley in a cross-sectional roughness curve of a reference length obtained by applying a phase compensation bandpass filter with cutoff values ​​λc and λs, and is specifically a value obtained in accordance with JIS B0601:2013. The upper limit of the ten-point average roughness of the metal layer can be adjusted by performing a smoothing treatment or not performing a roughening treatment on the surface of the metal layer depending on the surface condition when the metal layer is obtained, and the lower limit can be adjusted by performing a roughening treatment or not performing a roughening treatment on the surface of the metal layer depending on the surface condition when the metal layer is obtained. As the methods of the smoothing treatment and the roughening treatment, respectively, there are two methods for obtaining the desired ten-point average roughness R zjis Examples of suitable methods include plating under conditions controlled according to the requirements.

[0015] The element average length R of at least one surface of the metal layer (in one embodiment, the surface in contact with the cured resin) sm is preferably 5.0 μm or more, or 9.0 μm or more, or 30.0 μm or more, or 50.0 μm or more from the viewpoint of improving the electrical properties of the metal clad laminate by reducing the skin resistance of the metal layer, and may be, for example, 100.0 μm or less, or 90.0 μm or less, or 80.0 μm or less from the viewpoint of further improving the adhesion between the resin cured product and the metal layer. smrepresents the average length of the profile curve elements in a cross-sectional roughness curve measured at a predetermined reference length (i.e., the average spacing between peaks), and is specifically a value calculated in accordance with JIS B0601:2013. Note that a peak or valley whose height is 10% or less of the maximum height or depth, and / or whose length is 1% or less of the length of the calculation section, is regarded as noise and recognized as part of the valley or peak that follows before or after. The lower limit of the average element length of the metal layer can be adjusted by performing a smoothing treatment or not performing a roughening treatment on the surface of the metal layer depending on the surface condition when the metal layer is obtained, and the upper limit can be adjusted by performing a roughening treatment or not performing a roughening treatment on the surface of the metal layer depending on the surface condition when the metal layer is obtained. The methods of smoothing and roughening are respectively set to obtain the desired average element length R sm Examples of suitable methods include plating under conditions controlled according to the requirements.

[0016] The static friction coefficient of the surface of the metal layer in contact with the cured resin is preferably 0.3 μs or more, or 0.33 μs or more, or 0.38 μs or more, in order to ensure better adhesion between the cured resin and the metal layer and form a fine and highly reliable wiring pattern when manufacturing a printed wiring board using the metal clad laminate, and is preferably 0.55 μs or less, or 0.50 μs or less, in order to smooth the surface of the metal layer and to improve adhesion between the metal layer and the cured resin. In the present disclosure, the static friction coefficient is a value determined by a method partially conforming to JIS P8147:2010 and described in the [Example] section of the present disclosure. The upper and lower limits of the static friction coefficient of the metal layer can be adjusted by subjecting the surface of the metal layer to rust prevention treatment, heat resistance treatment, silane coupling treatment, formation of another metal layer, formation of a chromate layer, or the like, depending on the surface condition of the metal layer when it is obtained.

[0017] <Cured resin> In one embodiment, the cured resin contains a structural moiety (sometimes referred to as a "heterocyclic compound-derived moiety" in the present disclosure) derived from a compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms (sometimes referred to simply as a "heterocyclic compound" in the present disclosure). In the cured resin, the heterocyclic compound-derived moiety is typically chemically bonded to a resin-derived moiety and / or a crosslinker-derived moiety. In a typical embodiment, the resin has a curable functional group (e.g., an ethylenically unsaturated group), and the polymerizable group of the heterocyclic compound and the curable functional group of the resin are addition polymerized.

[0018] In one embodiment, the cured resin is a cured resin composition containing the heterocyclic compound (A) of the present embodiment, a resin (B), a polymerization initiator (C), and a crosslinking agent (D). The resin composition may further contain at least one of a solvent, various additives, and the like.

[0019] In order to form a metal clad laminate having good electrical properties, the dielectric constant and the dielectric loss tangent of the cured resin are controlled to be equal to or less than a predetermined value. The dielectric constant and the dielectric loss tangent may be controlled by selecting the blending components of the resin composition, which is the material of the cured resin, in particular by selecting the combination of the resin, the polymerization initiator, and the crosslinking agent.

[0020] In one embodiment, the dielectric constant of the cured resin is 3.3 or less, or 3.2 or less, or 3.0 or less. The lower the dielectric constant, the more preferable. However, from the viewpoint of ease of production of the cured resin, the dielectric constant may be, for example, 2.2 or more, or 2.5 or more, or 2.8 or more.

[0021] In one embodiment, the dielectric loss tangent of the cured resin is 0.003 or less, or 0.0025 or less, or 0.0020 or less. The lower the dielectric loss tangent, the more preferable it is. However, from the viewpoint of ease of production of the cured resin, the dielectric loss tangent may be, for example, 0.0025 or more, or 0.0027 or more, or 0.0028 or more.

[0022] The cured resin is required to have high solder reflow heat resistance and through-hole reliability, which are necessary for substrate materials for printed wiring boards. The glass transition temperature (Tg) derived from the crosslink density of the cured resin is an indicator of these performances. The glass transition temperature of the cured resin corresponds to the glass transition temperature of the cured resin obtained by curing under typical conditions of use such as heating and pressure when forming a laminate of the cured resin. In particular, from the viewpoint of exhibiting good heat resistance of the cured resin (especially solder heat resistance corresponding to lead-free solder), the glass transition temperature of the cured resin is preferably 170°C or higher, more preferably 180°C or higher, and more preferably 190°C or higher. Although the glass transition temperature of the cured resin is preferably high, from the viewpoints of applicability to the use environment of the cured resin and adhesion between the cured resin and metal foil, the glass transition temperature of the cured resin is preferably 300°C or lower, more preferably 270°C or lower.

[0023] [Heterocyclic compound (A)] The structural portion derived from a compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms contributes to good adhesion between the resin cured product and the metal layer. Without being bound by theory, it is believed that when a laminate of a metal cured product and a metal layer is formed using a resin composition containing a compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms, and a resin, the polymerizable group in the heterocyclic compound forms a stable bond with the resin in the resin composition, and the nitrogen-containing heterocycle in the heterocyclic compound interacts with the metal layer (in one embodiment, forms a complex), and as a result, the resin cured product having a portion derived from the heterocyclic compound can exhibit extremely good adhesion even to the metal layer of this embodiment, whose surface in contact with the resin cured product has a low roughness.

[0024] The polymerizable group of the heterocyclic compound is typically an ethylenically unsaturated group, such as an acrylic group, a methacrylic group, or an ethacrylic group, and is preferably a methacrylic group.

[0025] The number of nitrogen atoms per heterocycle in the heterocyclic compound is 1 or more in one embodiment, preferably 2 or more, 3 or more, or 4 or more, particularly preferably 3 or 4, from the viewpoint of good interaction between the heterocyclic compound and the metal layer. The heterocyclic compound may have one or more nitrogen-containing heterocycles, and preferably has one nitrogen-containing heterocycle from the viewpoint of maintaining good dielectric properties of the resin cured product. The heterocyclic compound may have a nitrogen-containing heterocycle and an aromatic ring that does not contain a nitrogen atom, and the aromatic ring that does not contain a nitrogen atom may or may not form a condensed ring with the nitrogen-containing heterocycle. The nitrogen-containing heterocycle in the heterocyclic compound may be, for example, a 5-membered ring or a 6-membered ring, and is preferably a 5-membered ring from the viewpoint of good interaction between the heterocyclic compound and the metal layer.

[0026] From the viewpoint of good interaction between the heterocyclic compound and the metal layer, the heterocyclic compound preferably has a triazole structure (more specifically, a 1,2,4-triazole structure) or a tetrazole structure, more preferably has an ethylenically unsaturated group and a triazole structure (more specifically, a 1,2,4-triazole structure) or a tetrazole structure, and even more preferably has an ethylenically unsaturated group, a triazole structure (more specifically, a 1,2,4-triazole structure) or a tetrazole structure, and a linking group linking them. Suitable examples of the ethylenically unsaturated group are as exemplified above. Suitable examples of the linking group are groups selected from the group consisting of -S- and -NH-.

[0027] The heterocyclic compound according to this embodiment is represented by the following general formula (1): [ka] {where, R 1 represents a hydrogen atom or a monovalent hydrocarbon group, R 2 is a hydrogen atom, a methyl group, or an ethyl group, and X is represented by the following general formula (X-1): [ka] (In the formula, R 3is a hydrogen atom or a monovalent hydrocarbon group.) or the following formula (X-2): [ka] or the following general formula (X-3): [ka] (In the formula, R 4 is a hydrogen atom or a monovalent hydrocarbon group; and Y is a sulfur atom or an NH group. It is expressed as:

[0028] The heterocyclic compound represented by general formula (1) is a compound having a triazole structure represented by general formula (X-1) or (X-2) or a tetrazole structure represented by general formula (X-3) and a metal constituting a metal layer, and a chemical bond of an acryloyl group, a methacryloyl group, or an ethacryloyl group to a resin having an ethylenically unsaturated group and / or a crosslinking agent, and a -OR group at the linking portion. 1 By controlling the polarity through modification, there is a tendency to achieve both adhesion between the metal layer surface and the substrate and rust prevention of the metal. This tendency is particularly noticeable when the metal layer surface is made of copper (Cu).

[0029] In the general formula (1), R 1 R is a hydrogen atom or a monovalent hydrocarbon group. 1The monovalent hydrocarbon group as a group may have 1 to 33 carbon atoms, may be substituted or unsubstituted, may be saturated or unsaturated, may be linear or cyclic, and / or may be aliphatic or aromatic. If linear, it may be linear or branched. If substituted, the substituent may be a monovalent aliphatic or aromatic group having 1 to 10 carbon atoms, such as methyl, ethyl, n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl groups; vinyl, allyl, propenyl, 3-butenyl, 2-butenyl, pentenyl, cyclopentenyl, hexenyl, cyclohexenyl, heptenyl, octenyl, nonenyl, decenyl, ethynyl, propynyl, butynyl, pentynyl, and hexynyl groups; cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups; phenyl, aryl, and benzyl groups.

[0030] R 1 Specific examples of monovalent hydrocarbon groups as groups may be substituted or unsubstituted aliphatic hydrocarbon groups having 1 to 20 carbon atoms, or substituted or unsubstituted aromatic groups having 6 to 24 carbon atoms.

[0031] R 1The substituted or unsubstituted aliphatic hydrocarbon group having 1 to 20 carbon atoms as a group preferably has 1 to 10, 1 to 15 or 4 to 12 carbon atoms when it is chain-like, and preferably has 3 to 18 or 3 to 20 carbon atoms when it is alicyclic. Specific examples of the substituted or unsubstituted aliphatic hydrocarbon group include methyl, ethyl, n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl groups. straight-chain or branched-chain alkyl groups; unsaturated aliphatic hydrocarbon groups such as vinyl, allyl, propenyl, 3-butenyl, 2-butenyl, pentenyl, cyclopentenyl, hexenyl, cyclohexenyl, heptenyl, octenyl, nonenyl, decenyl, ethynyl, propynyl, butynyl, pentynyl, and hexynyl groups; and cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups.

[0032] R 1 Specific examples of the substituted or unsubstituted aromatic group having 6 to 24 carbon atoms as the group include a phenyl group, an aryl group, a benzyl group, a naphthyl group, an anthryl group, and a phenanthryl group.

[0033] In order to prevent an adherent on the surface of the metal layer from deteriorating the dielectric properties of the metal clad laminate, R 1 is preferably a hydrogen (H) atom. 1 is -OH, the linkage between the triazole structure or tetrazole structure and the acryloyl group, methacryloyl group or ethacryloyl group is modified with -OH, and thus, even if the heterocyclic compound represented by general formula (1) is contained in a resin composition for forming a resin cured product, which is the adherend, an increase in the dielectric tangent of the adherend can be suppressed.

[0034] In the general formula (1), R 2is a hydrogen atom, a methyl group, or an ethyl group. From the viewpoint of availability of synthetic raw materials for the heterocyclic compound represented by general formula (1), a hydrogen atom or a methyl group is preferable. From the viewpoint of protection of the metal layer surface from corrosion or rust and improvement of adhesion to the adherend, a methyl group is preferable. From the viewpoint of bulkiness of the obtained heterocyclic compound, an ethyl group is preferable.

[0035] In general formula (1), Y is a sulfur (S) atom or an NH group, and forms -S- or -NH- as a linking moiety between the triazole structure or tetrazole structure and the acryloyl group, methacryloyl group or ethacryloyl group.

[0036] In the general formula (1), the presence of the linking portion Y is determined by a triazole structure or a tetrazole structure capable of forming a complex with the metal in the metal layer (copper (Cu) in one embodiment), an acryloyl group, a methacryloyl group, or an ethacryloyl group capable of chemically bonding to the constituent resin of the resin composition, and a -OR 1 By allowing the modified moiety to coexist in one molecule, it is possible to improve the adhesive strength between the cured resin material containing the molecule and the surface of the metal layer while suppressing an increase in the dielectric tangent of the cured resin material.

[0037] In general formula (1), X is a triazole structure represented by general formula (X-1) or formula (X-2), or a tetrazole structure represented by general formula (X-3). That is, in the case of a triazole structure, X is a monovalent group having a substituted or unsubstituted 1,2,4-triazole skeleton represented by general formula (X-1), or a monovalent group derived from 3-amino-1,2,4-triazole represented by formula (X-2), and in the case of a tetrazole structure, X is a monovalent group derived from a substituted or unsubstituted tetrazole represented by general formula (X-3).

[0038] In the 1,2,4-triazole ring in the general formula (X-1), the linking portion to Y in the general formula (1) and R 3 Their relative positions are 3rd and 5th, or vice versa.

[0039] In general formula (X-1), R 3 R is a hydrogen atom or a monovalent hydrocarbon group. 3 When is a hydrogen atom, the unsubstituted 1,2,4-triazole group that is a monovalent group represented by general formula (X-1) can be linked to Y in general formula (1) at the 3-position in the 1,2,4-triazole ring.

[0040] R 3 The monovalent hydrocarbon group as a group may have 1 to 33 carbon atoms, may be substituted or unsubstituted, may be saturated or unsaturated, may be linear or cyclic, and / or may be aliphatic or aromatic. If linear, it may be linear or branched. If substituted, the substituent may be a monovalent aliphatic or aromatic group having 1 to 10 carbon atoms, such as methyl, ethyl, n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl groups; vinyl, allyl, propenyl, 3-butenyl, 2-butenyl, pentenyl, cyclopentenyl, hexenyl, cyclohexenyl, heptenyl, octenyl, nonenyl, decenyl, ethynyl, propynyl, butynyl, pentynyl, and hexynyl groups; cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups; phenyl, aryl, and benzyl groups.

[0041] R 3 Specific examples of monovalent hydrocarbon groups as groups may be substituted or unsubstituted aliphatic hydrocarbon groups having 1 to 20 carbon atoms, or substituted or unsubstituted aromatic groups having 6 to 24 carbon atoms.

[0042] R 3The substituted or unsubstituted aliphatic hydrocarbon group having 1 to 20 carbon atoms as a group preferably has 1 to 10, 1 to 15 or 4 to 12 carbon atoms when it is chain-like, and preferably has 3 to 18 or 3 to 20 carbon atoms when it is alicyclic. Specific examples of the substituted or unsubstituted aliphatic hydrocarbon group include methyl, ethyl, n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl groups. straight-chain or branched-chain alkyl groups; unsaturated aliphatic hydrocarbon groups such as vinyl, allyl, propenyl, 3-butenyl, 2-butenyl, pentenyl, cyclopentenyl, hexenyl, cyclohexenyl, heptenyl, octenyl, nonenyl, decenyl, ethynyl, propynyl, butynyl, pentynyl, and hexynyl groups; and cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups.

[0043] R 3 Specific examples of the substituted or unsubstituted aromatic group having 6 to 24 carbon atoms as the group include a phenyl group, an aryl group, a benzyl group, a naphthyl group, an anthryl group, and a phenanthryl group.

[0044] The monovalent group represented by formula (X-2) is substituted with an amino group at the 3-position of the 1,2,4-triazole ring and can be linked to Y in general formula (1) at the 5-position.

[0045] The monovalent group represented by general formula (X-3) can be linked to Y in general formula (1) at the 5-position in the tetrazole ring.

[0046] In general formula (X-3), R 4 is a hydrogen atom or a monovalent hydrocarbon group.

[0047] R 4The monovalent hydrocarbon group as a group may have 1 to 33 carbon atoms, may be substituted or unsubstituted, may be saturated or unsaturated, may be linear or cyclic, and / or may be aliphatic or aromatic. If linear, it may be linear or branched. If substituted, the substituent may be a monovalent aliphatic or aromatic group having 1 to 10 carbon atoms, such as methyl, ethyl, n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl groups; vinyl, allyl, propenyl, 3-butenyl, 2-butenyl, pentenyl, cyclopentenyl, hexenyl, cyclohexenyl, heptenyl, octenyl, nonenyl, decenyl, ethynyl, propynyl, butynyl, pentynyl, and hexynyl groups; cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups; phenyl, aryl, and benzyl groups.

[0048] R 4 Specific examples of monovalent hydrocarbon groups as groups may be substituted or unsubstituted aliphatic hydrocarbon groups having 1 to 20 carbon atoms, or substituted or unsubstituted aromatic groups having 6 to 24 carbon atoms.

[0049] R 4The substituted or unsubstituted aliphatic hydrocarbon group having 1 to 20 carbon atoms as a group preferably has 1 to 10, 1 to 15 or 4 to 12 carbon atoms when it is chain-like, and preferably has 3 to 18 or 3 to 20 carbon atoms when it is alicyclic. Specific examples of the substituted or unsubstituted aliphatic hydrocarbon group include methyl, ethyl, n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl groups. straight-chain or branched-chain alkyl groups; unsaturated aliphatic hydrocarbon groups such as vinyl, allyl, propenyl, 3-butenyl, 2-butenyl, pentenyl, cyclopentenyl, hexenyl, cyclohexenyl, heptenyl, octenyl, nonenyl, decenyl, ethynyl, propynyl, butynyl, pentynyl, and hexynyl groups; and cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups.

[0050] R 4 Specific examples of the substituted or unsubstituted aromatic group having 6 to 24 carbon atoms as the group include a phenyl group, an aryl group, a benzyl group, a naphthyl group, an anthryl group, and a phenanthryl group.

[0051] The molecular weight of the heterocyclic compound represented by the general formula (1) is determined by X, Y, and R. 1 , R 2 , R 3 or R 4 For example, the range is 200 to 1,030, 200 to 830, 200 to 630, 200 to 530, 200 to 430, 200 to 380, or 200 to 330.

[0052] The heterocyclic compound represented by the general formula (1) can improve the adhesion between a cured resin product and a metal layer surface, and optionally suppress deterioration of the dielectric properties of the cured resin product and / or metal corrosion or rust of a metal clad laminate, and therefore, can be satisfactorily used as a heterocyclic compound represented by the following general formula (1-1): [ka] {where, R 1 and R 2is as defined for general formula (1), and R 3 is as defined for general formula (X-1).}, a heterocyclic compound represented by the following general formula (1-2): [ka] {where, R 1 and R 2 is as defined for general formula (1).} and a heterocyclic compound represented by the following general formula (1-3): [ka] {where, R 1 and R 2 is as defined for general formula (1), and R 4 is as defined for general formula (X-3).

[0053] The heterocyclic compound is particularly preferably a heterocyclic compound represented by the general formula (1-1): 1 and R 3 is a hydrogen atom, 1 is a hydrogen atom, and 1 and R 4 is a hydrogen atom.

[0054] <Method for producing heterocyclic compounds> In the method for producing a heterocyclic compound according to the present embodiment, for example, a cleavage reaction of an epoxide, an addition reaction of an epoxide, a ring-opening reaction of an oxirane, a reaction between an amine and an epoxide, a reaction between a thiol and an epoxide, a (partial) crosslinking reaction or a curing reaction of an epoxy compound, promotion of the reaction of an epoxide by an imidazole or a tetrazole, promotion of the reaction of a thiol and an epoxide by a tertiary amine, promotion of a reaction by other catalytic actions, and the like can be used alone or in combination.

[0055] Specifically, the compound is a compound obtained by mixing glycidyl acrylate (GA), glycidyl methacrylate (GMA), glycidyl ethacrylate (GEA), or any combination thereof (hereinafter, collectively referred to as a "glycidyl (alkyl) acrylate compound") with a compound represented by the following formula: X-SH, where X is as defined in general formula (1) above; and / or X-NH 2 {wherein X is as defined in general formula (1) above} The heterocyclic compound represented by the above general formula (1) can be obtained by reacting the compound represented by the above general formula (1) with a compound represented by the above general formula (1).

[0056] As the glycidyl (alkyl) acrylate compound, GA, GMA, GEA or any combination thereof is represented by the general formula (1) 2 From the viewpoint of availability of raw materials, GA or GMA is preferred, from the viewpoint of protection of the metal layer surface from corrosion or rust and improvement of adhesion to the adherend, GMA is preferred, and from the viewpoint of bulkiness of the reaction product, GEA is preferred.

[0057] Glycidyl (alkyl) acrylate compounds and compounds of the formula X-SH and / or X-NH 2 For the reaction with a compound represented by the formula (I), it is preferable to use an organic solvent as a reaction solvent, and for example, one or more selected from ketones such as acetone; alcohols such as methanol and ethanol; and glycol-based solvents such as glycol ether, propylene glycol monomethyl ether, and propylene glycol monomethyl ether acetate may be used.

[0058] Regarding the reaction conditions, the reaction temperature may be normal temperature or room temperature, for example, within a range of 15°C to 40°C or 20°C to 35°C, the reaction time may be within a range of 3 hours to 120 hours, 4 hours to 118 hours, 4 hours to 50 hours, or 6 hours to 25 hours, and the reaction atmosphere is preferably under draft drying or vacuum drying.

[0059] After completion of the reaction, from the viewpoint of improving the yield of the product or identifying the product, for example, filtration, evaporation to dryness, vacuum drying, standing, decantation, precipitation, redissolution, reprecipitation, gel permeation chromatography (GPC), nuclear magnetic resonance (NMR) measurement, etc. can be performed alone or in appropriate combination to separate the product.

[0060] Glycidyl (alkyl) acrylate compounds and compounds of the formula X-SH and / or X-NH 2 In the reaction with a compound represented by the general formula (1), R 1 In general, it is easier to obtain heterocyclic compounds in which the ring atom is a hydrogen (H) atom.

[0061] In general formula (1), R 1 In the case where R is a monovalent hydrocarbon, (i) 1 OH (However, R 1 is a monovalent hydrocarbon) to form -OR during ring opening of the epoxide. 1 Group (wherein R 1 (ii) a process for forming a product or intermediate having general formula (1), 1 The -OH group of a heterocyclic compound, which is =H, is converted to a sodium alkoxide (-O - Na + ), and then reacting with a halogen compound such as an alkyl halide or with a halogen compound such as an alkyl halide in the presence of a tertiary amine such as triethylamine to give -OR 1 Group (wherein R 1 is a monovalent hydrocarbon).

[0062] A glycidyl (alkyl) acrylate compound and a compound of the formula X-SH or X-NH 2 In the reaction with a compound represented by the formula X-SH or X-NH, the molar ratio of the two (glycidyl (alkyl) acrylate compound: 2From the viewpoint of improving the yield of the product or suppressing the isomerization reaction, the ratio of the aryl group to the alkyl group is preferably 1:1.0 to 1.3, or 1:1.0 to 1.2, and more preferably 1:1.0 to 1.1.

[0063] As the reactant with the glycidyl (alkyl) acrylate compound, when X has a triazole structure, a compound represented by the formula X-SH is preferred, and when X has a tetrazole structure, a compound represented by the formula X-NH 2 Preferred is a compound represented by the following formula:

[0064] When X has a triazole structure, the compound represented by the formula X-SH is represented by the following formula (2): [ka] {where, R 3 is as defined in formula (X-1) above. or 3-amino-5-mercapto-1,2,4-triazole, and more preferably 3-mercapto-1,2,4-triazole or 3-amino-5-mercapto-1,2,4-triazole.

[0065] Formula X-NH 2 When X has a tetrazole structure, the compound represented by the formula (I) is preferably 5-aminotetrazole.

[0066] Glycidyl (alkyl) acrylate compounds and compounds of formula X-SH and / or X-NH 2 In the reaction with a compound represented by the formula X-SH or X-NH, it is preferable to use a basic catalyst or a strong basic catalyst. When using a basic catalyst or a strong basic catalyst, the molar ratio of the glycidyl (alkyl) acrylate compound to the catalyst (glycidyl (alkyl) acrylate compound: catalyst) is preferably 1:0.09 to 0.13, more preferably 1:0.10 to 0.13, from the viewpoint of suppressing the production of isomers. From the same viewpoint, the reaction of the glycidyl (alkyl) acrylate compound with a compound represented by the formula X-SH or X-NH 2The molar ratio of the compound represented by the formula X-SH or X-NH to the catalyst (glycidyl (alkyl) acrylate compound: 2 The ratio of the compound represented by the formula (I):catalyst) is preferably 1:1.0-1.3:0.09-0.13.

[0067] Without wishing to be bound by theory, it is known that primary, secondary and tertiary amino groups have significantly different reactivity with epoxy groups, with primary amino groups being the most reactive, secondary amino groups being the least reactive, and tertiary amines having no active hydrogen, so they do not react with epoxy groups but are thought to function as catalysts for the reaction between epoxy groups or between epoxy groups and other functional groups (e.g., primary amino groups, mercapto groups, alcoholic hydroxyl groups, etc.). Thus, when a tertiary amine such as triethylamine (TEA) is used as a basic catalyst, the reaction of the mercapto group can be promoted by the catalytic action of the tertiary amine, or the tertiary amine can be used catalytically without inhibiting the reaction between a compound having a primary amino group and a glycidyl (alkyl) acrylate compound.

[0068] In addition, it has been found that when a tertiary amine such as TEA is used as a catalyst in the reaction for obtaining the heterocyclic compound according to this embodiment, the isomerization reaction is suppressed, and the yield of the specified heterocyclic compound tends to be easily improved.

[0069] In the reaction for obtaining the heterocyclic compound according to this embodiment, when it is desired to suppress the progress of the crosslinking reaction or curing reaction of the epoxy group derived from GA, GMA, GEA, or a combination thereof, it is preferable to avoid the inclusion of a polyfunctional compound such as a polyamino compound or a polymercapto compound.

[0070] On the other hand, depending on the application of the heterocyclic compound according to this embodiment, it may be preferable to proceed with a crosslinking reaction or a curing reaction of the epoxy group derived from 2 moles of a glycidyl (alkyl) acrylate compound. In this case, it is preferable to promote a curing reaction or a crosslinking reaction between the heterocyclic compound and another crosslinking agent during or after the reaction to obtain the heterocyclic compound, in situ or in a separate reaction system, to form a cured product or a crosslinked network containing a structural unit derived from the heterocyclic compound.

[0071] The structure of the heterocyclic compound-derived moiety in the cured resin can be confirmed by solid-state NMR measurement.

[0072] The respective ratios of the heterocyclic compound (A) in the resin composition and the heterocyclic compound (A)-derived sites in the cured resin are preferably 0.01 mass% or more, or 0.02 mass% or more, or 0.03 mass% or more, and preferably 1.0 mass% or less, or 0.5 mass% or less, or 0.3 mass% or less.

[0073] [Resin (B)] The resin (B) contained in the resin composition typically has a curable functional group in the molecule, preferably at the molecular end. The curable functional group contributes to improving the adhesion between the resin cured product and the metal layer by bonding with the polymerizable group of the heterocyclic compound (A). The curable functional group of the resin (B) is preferably an ethylenically unsaturated group, since it can form a stable bond with the polymerizable group of the heterocyclic compound (A). The number of curable functional groups per molecule of the resin (B) is preferably 2 to 5, or 2 to 4, or 2 or 3, or 3, since the physical properties, dielectric properties, and adhesion to the metal layer of the resin cured product are good.

[0074] In terms of being able to easily control the dielectric constant and dielectric loss tangent of the cured resin within the desired range of this embodiment, the resin (B) is preferably at least one resin selected from the group consisting of polyphenylene ether (PPE), polystyrene, a resin having an alicyclic structure, a polybenzoxazole precursor resin, a polyimide precursor resin, and a phenol resin, and particularly preferably polyphenylene ether.

[0075] The mass ratio (A:B) of the heterocyclic compound (A) to the resin (B) in the resin composition is preferably 1:7 to 50, or 1:8 to 46, or 1:9 to 44, from the viewpoint of obtaining good adhesion between the cured resin and the metal layer.

[0076] (Polyphenylene ether) In a preferred embodiment, the resin (B) is a polyphenylene ether. In one embodiment, the polyphenylene ether is represented by the following general formula (3): [ka] {where, R a , R b , R c and R d each independently represents a hydrogen atom, a halogen atom (e.g., a fluorine atom, a chlorine atom, and a bromine atom), an alkyl group which may have a substituent (e.g., a linear or branched alkyl group having 1 to 6 carbon atoms such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a tert-butyl group, etc., and a cyclic alkyl group having 6 to 10 carbon atoms such as a cyclohexyl group), an alkoxy group which may have a substituent (e.g., an alkoxy group having 1 to 6 carbon atoms such as a methoxy group, an ethoxy group, a butoxy group, etc.), an aryl group which may have a substituent (e.g., a phenyl group and a naphthyl group), an amino group which may have a substituent, a nitro group which may have a substituent, or a carboxyl group which may have a substituent.} However, the above-mentioned substituents are each a group having 0 to 6 carbon atoms, and are preferably not present.

[0077] The presence of polyphenylene ether in the cured resin can be confirmed by observing the following peaks in the spectrum obtained by FT-IR measurement (ATR method) of the cured resin: 1021, 1189, 1306, 1471, 1603 cm -1 This can be confirmed by detecting a relatively strong peak in the vicinity.

[0078] Specific examples of polyphenylene ethers include poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), copolymers of 2,6-dimethylphenol and other phenols (e.g., 2,3,6-trimethylphenol, 2-methyl-6-butylphenol, etc.), and polyphenylene ether copolymers obtained by coupling 2,6-dimethylphenol with biphenols or bisphenols, and polyphenylene ethers having a linear or branched structure obtained by heating poly(2,6-dimethyl-1,4-phenylene ether) or the like in the presence of a phenolic compound such as a bisphenol or trisphenol and an organic peroxide in a solvent such as toluene to cause a redistribution reaction.

[0079] Among these polyphenylene ethers, polyphenylene ethers having a branched structure in the molecular chain are preferred because the phenylene groups are difficult to stack, making it difficult to form hard segments, and as a result, they tend to have high thermal shock resistance. Examples of such polyphenylene ethers include polyphenylene ether copolymers obtained by coupling monofunctional phenols such as 2,6-dimethylphenol and 2,3,6-trimethylphenol with multifunctional phenol compounds having a branched structure such as tris(4-hydroxyphenyl)methane, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,1,1-tris(4-hydroxyphenyl)ethane, and α,α,α',α'-tetrakis(4-hydroxyphenyl)-p-xylene; and polyphenylene ethers having a branched structure, which are obtained by heating poly(2,6-dimethyl-1,4-phenylene ether) or the like in the presence of a phenol compound having a branched structure, such as tris(4-hydroxyphenyl)methane, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,1,1-tris(4-hydroxyphenyl)ethane, α,α,α',α'-tetrakis(4-hydroxyphenyl)-p-xylene, and an organic peroxide, in a solvent such as toluene, to cause a redistribution reaction.

[0080] When the polyphenylene ether has a linear structure, the number average molecular weight is preferably 500 to 15,000, or 700 to 5,000, or 2,000 to 2,700, or 2,300 to 2,450. When the polyphenylene ether contains a branched structure, the number average molecular weight is preferably 500 to 15,000, or 700 to 5,000, or 1,000 to 3,000, or 1,450 to 2,800. The smaller the weight average molecular weight Mw / number average molecular weight Mn ratio of the polyphenylene ether, the higher the fluidity of the resin composition and the wettability to the metal layer, which is preferable from the viewpoint of adhesion between the cured resin and the metal layer. Specifically, the Mw / Mn ratio is preferably 1.1 to 5.0, or 1.2 to 3.0, or 1.3 to 2.0, or 1.35 to 1.40. The number average molecular weight and weight average molecular weight of polyphenylene ether are values ​​determined by gel permeation chromatography in terms of standard polystyrene.

[0081] The curable functional group that polyphenylene ether typically has is preferably present at the molecular terminal from the viewpoint of obtaining good properties of the resin cured material (adhesion to a metal layer, physical properties such as heat resistance, dielectric properties, etc.) by crosslinking and bonding with a heterocyclic compound. In one embodiment, the polyphenylene ether has two or more terminal curable functional groups, and can form a crosslinked structure in the resin cured material by crosslinking the polyphenylene ether.

[0082] The polyphenylene ether is preferably represented by the following general formula (4): [ka] In the formula, n is 0 or 1, and R e represents a saturated or unsaturated alkylene group having 1 to 8 carbon atoms, and R f represents a hydrogen atom, or a saturated or unsaturated alkyl group having 1 to 8 carbon atoms.} (i.e., a site containing an ethylenically unsaturated group as a curable functional group).

[0083] In the general formula (4), n is preferably 0, and the structure of the curable site is preferably R r As C 1-8 An α,β-unsaturated carboxylic acid ester group having an alkyl group is preferred. As such an α,β-unsaturated carboxylic acid ester group, an acrylate group, a methacrylate group, an ethacrylate group, a propacrylate group, or a butacrylate group is preferred.

[0084] When introducing the above-mentioned unsaturated carboxylic acid ester group into the polyphenylene ether molecule terminal, the introduction method is not limited, and an example is the formation of an ester bond between the hydroxyl group at the terminal of the polyphenylene ether and the unsaturated carboxylic acid. Various known methods can be used to form the ester bond. For example, a. reaction between a carboxylic acid halide and a polymer terminal hydroxyl group, b. formation of an ester bond by reaction between a carboxylic acid anhydride and a polymer terminal hydroxyl group, c. direct reaction between a carboxylic acid and a polymer terminal hydroxyl group, d. a method using an ester exchange reaction, etc. can be mentioned.

[0085] The polyphenylene ether preferably has 2 or more curable functional groups in one molecule, more preferably 2.5 to 5.0 or 2.5 to 4.0 on average. When the average number of curable functional groups in one molecule of the polyphenylene ether is large, the heat resistance tends to be high, and when the average number of curable functional groups is small, the toughness tends to be high. When the average number of curable functional groups is 2.5 or more, the heat resistance of the metal clad laminate tends to be good, and when it is 5.0 or less, the flowability of the resin composition is good, and the adhesion between the resin cured product and the metal layer and the uniformity of the metal clad laminate tend to be high.

[0086] When the polyphenylene ether has a curable functional group, the curing rate of the polyphenylene ether is preferably 30% or more, or 50% or more, or 80% or more, or 85% or more, or 90% or more from the viewpoint of high heat resistance, low water absorption, etc. The curing rate of the polyphenylene ether may be 100%, but from the viewpoint of ease of production of the cured resin, it may be, for example, less than 100%, or 99% or less, or 98% or less. The curing rate can be determined by solid-state NMR measurement of a pulverized sample of the cured resin.

[0087] The respective ratios of the resin (B) in the resin composition and the resin (B)-derived sites in the cured resin are preferably 20% by mass or more, or 30% by mass or more, or 40% by mass or more, or 50% by mass or more, or 60% by mass or more, and preferably 90% by mass or less, or 80% by mass or less, or 70% by mass or less, or 60% by mass or less, or 50% by mass or less.

[0088] [Polymerization initiator (C)] The resin composition typically contains a polymerization initiator (C). As the polymerization initiator (C), any organic peroxide capable of promoting the curing reaction in the resin composition can be used. From the viewpoint of good progress of the curing reaction, at least one selected from the group consisting of oxime esters and peroxides is preferred.

[0089] Examples of oxime esters include 1-phenyl-1,2-propanedione-2-O-benzoyloxime, 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, and the like.

[0090] The peroxide is preferably an organic peroxide, and examples thereof include benzoyl peroxide, cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, di-t-butyl peroxide, t-butylcumyl peroxide, di(2-t-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, dicumyl peroxide, di-t-butylperoxyisophthalate, t-butylperoxybenzoate, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, di(trimethylsilyl)peroxide, and trimethylsilyltriphenylsilyl peroxide. In addition, radical generators such as 2,3-dimethyl-2,3-diphenylbutane can also be used as reaction initiators for the resin composition. Among them, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, di(2-t-butylperoxyisopropyl)benzene, and 2,5-dimethyl-2,5-di(t-butylperoxy)hexane are preferred from the viewpoint of providing a resin cured product having excellent heat resistance and mechanical properties, and further low relative dielectric constant and dielectric loss tangent.

[0091] The content of the polymerization initiator (C), based on the total content of the heterocyclic compound (A) and the resin (B) being 100% by mass, is preferably 0.05% by mass or more, or 0.5% by mass or more, or 1% by mass or more, or 1.5% by mass or more from the viewpoint of good reaction efficiency, and is preferably 5% by mass or less, or 4.5% by mass or less, or 4.0% by mass or less from the viewpoint of keeping the relative dielectric constant and dielectric tangent of the cured resin low.

[0092] [Crosslinker (D)] In one embodiment, the resin composition contains a crosslinking agent (D), and the cured resin further has a crosslinked structure formed by crosslinking the crosslinking agent. Any crosslinking agent capable of initiating or promoting a crosslinking reaction can be used as the crosslinking agent (D). From the viewpoint of the crosslinking reaction, the crosslinking agent preferably has an average of two or more carbon-carbon unsaturated double bonds in one molecule. The crosslinking agent may be composed of one type of compound, or may be composed of two or more types of compounds. In this specification, the term "carbon-carbon unsaturated double bond" refers to a double bond located at an end branched from the main chain when the crosslinking agent is a polymer or oligomer. An example of the carbon-carbon unsaturated double bond is a 1,2-vinyl bond in polybutadiene.

[0093] Examples of the crosslinking agent (D) include trialkenyl isocyanurate compounds such as triallyl isocyanurate (TAIC), trialkenyl cyanurate compounds such as triallyl cyanurate (TAC), polyfunctional methacrylate compounds having two or more methacrylic groups in the molecule, polyfunctional acrylate compounds having two or more acrylic groups in the molecule, polyfunctional vinyl compounds having two or more vinyl groups in the molecule such as polybutadiene, vinylbenzyl compounds such as divinylbenzene having a vinylbenzyl group in the molecule, and polyfunctional maleimide compounds having two or more maleimide groups in the molecule such as 4,4'-bismaleimide diphenylmethane. These crosslinking agents are used alone or in combination of two or more. Of these, the crosslinking agent preferably contains at least one compound selected from the group consisting of triallyl cyanurate, triallyl isocyanurate, and polybutadiene.

[0094] The amount of crosslinking agent (D) based on the total content of the heterocyclic compound (A) and the resin (B) in the resin composition (100% by mass), or the amount of sites derived from crosslinking agent (D) based on the total content of the sites derived from the heterocyclic compound (A) and the sites derived from the resin (B) in the cured resin product (100% by mass), is, from the viewpoint of obtaining good physical properties of the cured resin product and good adhesion to the metal layer, preferably 10% by mass or more, or 15% by mass or more, or 20% by mass or more, or 30% by mass or more, and from the viewpoint of keeping the relative dielectric constant and dielectric tangent of the cured resin product low, is preferably 50% by mass or less, or 40% by mass or less, or 30% by mass or less.

[0095] [Additives] The resin composition may further contain one or more additives selected from the group consisting of an elastomer different from the above-mentioned resin (B), a flame retardant, an inorganic filler (e.g., silica filler, etc.), a heat stabilizer, an antioxidant, a UV absorber, a surfactant, a lubricant, etc. The content of the additive is preferably 0.01 to 100 mass%, more preferably 0.1 to 80 mass%, and even more preferably 1 to 50 mass%, based on 100 mass% of the total content of the heterocyclic compound (A) and the resin (B) in the resin composition, or based on 100 mass% of the total content of the heterocyclic compound (A) and the resin (B) in the cured resin.

[0096] (Elastomer) The elastomer different from the resin (B) is preferably at least one selected from the group consisting of a block copolymer of a vinyl aromatic compound and an olefin-based alkene compound, its hydrogenation product (a hydrogenated block copolymer obtained by hydrogenating a block copolymer of a vinyl aromatic compound and an olefin-based alkene compound), and a homopolymer of a vinyl aromatic compound. In the block copolymer or its hydrogenation product, the content of the unit derived from the vinyl aromatic compound is preferably 2% by mass or more, or 3% by mass or more, or 5% by mass or more, or 10% by mass or more, or 20% by mass or more, in terms of good adhesion between the resin cured product and the metal layer due to good compatibility between the resin (B) and the elastomer, and can be, for example, 80% by mass or less, 75% by mass or less, or 70% by mass or less depending on the desired application.

[0097] The vinyl aromatic compound may have an aromatic ring and a vinyl group in the molecule, such as styrene. The olefin alkene compound may have a linear or branched structure in the molecule, such as ethylene, propylene, butylene, isobutylene, butadiene, and isoprene. When the resin (B) is polyphenylene ether, from the viewpoint of excellent compatibility with the polyphenylene ether, the elastomer is preferably at least one selected from the group consisting of styrene-butadiene block copolymers, styrene-ethylene-butadiene block copolymers, styrene-ethylene-butylene block copolymers, styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-butadiene-butylene block copolymers, styrene-isoprene block copolymers, styrene-ethylene-propylene block copolymers, styrene-isobutylene block copolymers; hydrogenated styrene-based elastomers such as hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-ethylene-butadiene block copolymers, hydrogenated SEBS, hydrogenated styrene-butadiene-butylene block copolymers, and hydrogenated styrene-isoprene block copolymers; and styrene homopolymers (polystyrene: PS), and more preferably at least one selected from the group consisting of styrene-butadiene block copolymers, SEBS, hydrogenated SEBS, and PS.

[0098] The hydrogenation rate in the hydrogenated product is not particularly limited, and some of the carbon-carbon unsaturated double bonds derived from the olefin-based alkene compound may remain.

[0099] The weight average molecular weight of the elastomer is preferably 30,000 to 300,000, more preferably 31,000 to 290,000. When the weight average molecular weight is 30,000 or more, the heat resistance of the resin cured product tends to be better, and when the weight average molecular weight is 300,000 or less, the fluidity of the resin composition tends to be better. The weight average molecular weight is a value determined by gel permeation chromatography in terms of standard polystyrene.

[0100] The amount of elastomer is preferably 2 mass% or more, or 3 mass% or more, or 4 mass% or more, based on the total content of resin (B) and crosslinking agent (D) in the resin composition (100 mass%), or based on the total content of sites derived from resin (B) and sites derived from crosslinking agent (D) in the resin cured product (100 mass%), in order to provide good dielectric properties of the cured resin and good adhesion to the metal layer, and is preferably 40 mass% or less, or 30 mass% or less, or 20 mass% or less, or 15 mass% or less in order to provide good fluidity of the resin composition.

[0101] (Flame retardant) The resin composition preferably contains a flame retardant. From the viewpoint of improving heat resistance, the flame retardant is preferably one that is incompatible with other components in the resin cured product after curing of the resin composition, particularly with the site derived from the resin (B) and the crosslinking agent (D). Examples of the flame retardant include inorganic flame retardants such as antimony trioxide, aluminum hydroxide, magnesium hydroxide, and zinc borate; aromatic bromine compounds such as hexabromobenzene, decabromodiphenylethane, 4,4-dibromobiphenyl, and ethylene bistetrabromophthalimide; and phosphorus-based flame retardants such as resorcinol bis-diphenyl phosphate and resorcinol bis-dixylenyl phosphate. These flame retardants are used alone or in combination of two or more. Among these, the flame retardant is preferably decabromodiphenylethane, which is more advantageous in terms of the dielectric properties of the resin cured product.

[0102] The content of the flame retardant is not particularly limited, but from the viewpoint of maintaining flame retardancy at the UL standard 94V-0 level, it is preferably 5 parts by mass or more, 10 parts by mass or more, or 15 parts by mass or more relative to 100 parts by mass of the total of the resin (B) and the crosslinking agent (D). Also, from the viewpoint of maintaining low relative dielectric constant and dielectric loss tangent of the resin cured product, the content of the flame retardant is preferably 50 parts by mass or less, 45 parts by mass or less, or 40 parts by mass or less.

[0103] [solvent] The resin composition may contain a solvent. In this case, the resin composition may be in the form of a varnish in which the solid components in the resin composition are dissolved or dispersed in the solvent. As the solvent, from the viewpoint of the solubility or dispersibility of the solid components, one or more selected from the group consisting of aromatic compounds such as toluene and xylene; alcohols such as methanol and ethanol; acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, propylene glycol monomethyl ether, and chloroform are suitable.

[0104] From the viewpoint of favorably dissolving the solid components in the resin composition, particularly the heterocyclic compound (A) and / or the resin (B) in the solvent and easily securing favorable fluidity of the resin composition even at room temperature, the solvent is more preferably an aromatic compound solvent such as toluene or xylene, and more preferably, for example, a toluene-methyl ethyl ketone mixed solvent, a toluene-cyclohexane mixed solvent, or a toluene-cyclopentanone mixed solvent, etc. From the viewpoint of impregnation into the substrate described below, toluene alone is also preferable as the solvent.

[0105] The amount of the solvent used can be arbitrarily determined depending on, for example, the desired viscosity of the resin composition, the means for applying the resin composition to the metal layer, the material and surface morphology of the metal layer, and the like.

[0106] <Base material> In the metal-clad laminate of this embodiment, a composite of a resin cured product and a substrate may be laminated with a metal layer. Examples of the substrate include various glass cloths such as roving cloth, cloth, chopped mat, and surfacing mat; asbestos cloth, metal fiber cloth, and other synthetic or natural inorganic fiber cloths; woven or nonwoven fabrics obtained from liquid crystal fibers such as fully aromatic polyamide fibers, fully aromatic polyester fibers, and polybenzoxazole fibers; natural fiber cloths such as cotton cloth, linen cloth, and felt; natural cellulose-based substrates such as carbon fiber cloth, craft paper, cotton paper, and cloth obtained from paper-glass mixed fiber yarn; and polytetrafluoroethylene porous films. These substrates are used alone or in combination of two or more.

[0107] The substrate is preferably a glass cloth. The dielectric constant of the glass cloth is preferably 5.1 or less, more preferably 4.9 or less. By using the glass cloth as the substrate, the metal clad laminate can have high heat resistance and low thermal expansion coefficient. In particular, when the dielectric constant of the glass cloth is 5.1 or less, the dielectric constant of the metal clad laminate can be further reduced compared to, for example, E glass cloth. The dielectric constant of the glass cloth is preferably low, but from the viewpoint of easy availability of the glass cloth, it may be, for example, Q glass or more, or L2 glass or more. The dielectric constant of the glass cloth is a value measured at 10 GHz by a cavity resonance method using a sample processed into a block, not a cloth.

[0108] <Production of Metal Clad Laminate> The metal clad laminate can be produced, for example, by laminating the resin composition of the present disclosure with a metal layer and curing the resin composition to obtain a resin cured product. Preferably, a resin film can be obtained by applying the resin composition in the form of a varnish alone or on a support, and then drying and removing the solvent in the resin composition to form a film. By laminating this resin film with a metal layer and further curing it, the resin film can function as an interlayer insulating sheet, an adhesive film, or the like in the metal clad laminate. A resin composition in the form of a varnish (hereinafter, also simply referred to as varnish) is preferred from the viewpoint of obtaining good adhesion between the resin cured product and the metal layer. In one embodiment, it is preferred to laminate a composite of a substrate and a resin composition as exemplified above (also referred to as "prepreg" in the present disclosure) on a metal layer and cure the resin composition. The prepreg can be obtained by impregnating the substrate with varnish and then drying and removing the solvent with a hot air dryer or the like.

[0109] The proportion of the resin composition solid content in the prepreg is preferably 30 to 80 mass%, more preferably 40 to 70 mass%. When the proportion of the resin composition solid content is 30 mass% or more, the metal clad laminate tends to have good insulation reliability. When the proportion of the resin composition solid content is 80 mass% or less, the metal clad laminate tends to have good mechanical properties such as flexural modulus.

[0110] In the metal-clad laminate according to one embodiment, a metal layer is laminated on one or both sides of the cured resin material, which may be composited with a substrate. The cured resin material may be laminated in contact with the metal layer, even when composited with a substrate. The lamination method is not particularly limited, and examples thereof include coating, applying, or spraying the resin composition on the substrate or metal layer; pasting or laminating the cured resin material with the substrate or metal layer; immersing the substrate or metal layer in the resin composition; impregnating the substrate or metal layer with the resin composition; transferring or replacing the resin composition from the support to the substrate, which will be described later; other composites; and drying the resin composition (particularly varnish). The application methods listed above can be used alone or in any combination. Examples of the support include polyolefins such as polyethylene, polypropylene, and polyvinyl chloride; polyesters such as polyethylene terephthalate and polyethylene naphthalate; polycarbonate; polyimide; metal foils such as copper foil and aluminum foil; and release paper. When the support is to be removed from the cured resin material afterwards, it may be subjected to chemical or physical treatments such as matte processing, corona treatment, and release treatment. On the other hand, when the support is made of a metal such as copper or aluminum, in one embodiment, the support may be used as the metal layer of the present disclosure.

[0111] A particularly preferred lamination method is to form the prepreg, layer it on a metal layer, and then cure the resin composition to obtain a metal clad laminate in which a composite of a cured resin and a substrate and a metal layer are laminated. The resin composition may be cured, for example, by heating at a temperature range of 140°C to 170°C and a hold time of 1 minute to 30 minutes. The composite to be combined with the metal layer may be one or more sheets, and a metal layer is layered on one or both sides of the composite depending on the application to process it into a metal clad laminate. One particularly preferred application of the metal clad laminate is a printed wiring board. It is preferable that at least a part of the metal foil is removed from the metal clad laminate to produce a printed wiring board.

[0112] <Characteristics of Metal Clad Laminate> In one aspect, the metal clad laminate of the present embodiment has the following characteristics (i) and / or (ii): (i) Peel strength of the cured resin against the metal layer is ≧0.4 N (ii) Df2 - Df1 ≦ 0.001 {In the formula, Df2 represents the dielectric loss tangent of a cured resin material containing a structural moiety derived from the heterocyclic compound of this embodiment, and Df1 represents the dielectric loss tangent of a cured resin material that is identical to the cured resin material described above but does not contain a structural moiety derived from the heterocyclic compound.} It is preferable that the above-mentioned properties (i) and (ii) are satisfied, and it is more preferable that the above-mentioned properties (i) and (ii) are satisfied.

[0113] Regarding the characteristic (i), the peel strength of the cured resin from the metal layer is preferably 0.4 N or more, more preferably 0.5 N or more, in terms of good adhesion of the cured resin to the metal layer in the metal clad laminate. The higher the peel strength, the more preferable it is, but from the viewpoint of ease of production of the metal clad laminate, it may be, for example, 1.0 N or less, or 0.8 N or less.

[0114] Regarding the characteristic (ii), the value obtained by subtracting Df1 from Df2 is an index showing the influence of the presence or absence of the heterocyclic compound of this embodiment, and when Df2-Df1≦0.001, the resin cured product tends to maintain good dielectric properties even if it has a structural part derived from the heterocyclic compound of this embodiment. From this viewpoint, Df2-Df1<0.0005 is more preferable. Although the value of Df2-Df1 is preferably small, from the viewpoint of ease of production of the metal clad laminate, it may be, for example, Df2-Df1≧0.0001 or Df2-Df1≧0.0002.

[0115] <Printed wiring board> The metal clad laminate of the present embodiment has excellent electrical properties, particularly high-frequency transmission properties, and is suitable as a material for electronic substrates. One aspect of the present invention provides a printed wiring board including the metal clad laminate of the present disclosure. In general, a printed wiring board refers to a board obtained by printing a conductor wiring pattern on the surface or inside of a plate made of an insulator, and refers to a state before forming an electrical component such as a capacitor. The printed wiring board according to the present embodiment may have, at least in a part thereof, the resin cured product of the present disclosure, an insulator, a conductor or its wiring pattern, a through hole or a blind via, etc. In one aspect, the printed wiring board is preferably a metal clad laminate from which a part of the metal foil has been removed, from the viewpoint of electrical properties. The printed wiring board of the present embodiment has the resin cured product of the present embodiment and the metal layer of the present embodiment that is well adhered to the resin cured product on the low-roughness surface, and thus can have excellent electrical properties and insulation reliability.

[0116] The printed wiring board of this embodiment can be typically formed by pressurizing and heating the prepreg of this embodiment described above, and then patterning the wiring of the metal layer of the laminate described above. The wiring patterning of the metal layer can be performed by, for example, physical etching, chemical etching, plating, immersion, etc.

[0117] The printed wiring board according to the present embodiment is particularly preferably mounted on a high-speed communication module because of its excellent electrical characteristics (particularly high-frequency transmission characteristics) and insulation reliability. The high-speed communication module is a terminal that can communicate information about a product, such as location information and operating status, at high speed by being incorporated into the product. Specifically, the high-speed communication module can be incorporated into a high-frequency transmission or fifth-generation (5G) communication system and used for information communication, remote control of industrial devices and equipment, Internet of Things (IoT), etc. EXAMPLES

[0118] The present embodiment will be specifically described below with reference to examples, but the present embodiment is not limited to the following examples in any way.

[0119] <Synthesis of heterocyclic compounds> The synthesis reaction was carried out according to the following scheme 1. [ka]

[0120] 52 g of acetone (non-volatile component concentration = 38.5%) was added to a three-neck flask as a solvent, 13.0 g of 3-mercapto-1,2,4-triazole (3MTA) and 18.27 g of glycidyl methacrylate (GMA) were added as reaction components, and 1.30 g of triethylamine (TEA) was added as a catalyst, and the reaction was carried out for 24 hours under draft drying. After that, the solvent was distilled off using an evaporator to obtain the product in the flask. The product was identified. 1 H-NMR (JEOL "ECS-400", dimethyl sulfoxide-D 6 (d6DMSO)) to obtain heterocyclic compound I. Note that isomer B is the heterocyclic compound represented by the formula (1-1) R 1 and R 3 is a hydrogen atom. Heterocyclic compound I 1 The H-NMR chart is shown in Figure 1.

[0121] Since the ratio of the peaks derived from methacrylates observed at around 5.7 ppm and 6.1 ppm in Figure 1 to the peak derived from the triazole ring at around 8.4 ppm was approximately 1:1, it was determined that heterocyclic compound I was obtained. The reason why the above ratio was not exactly 1:1 is presumably because a mixture of isomer A and isomer B was obtained, rather than a single type of compound.

[0122] <Preparation of denatured PPE1> A 1.5-liter jacketed reactor equipped with a sparger for introducing an oxygen-containing gas at the bottom of the reactor, stirring turbine blades and a baffle, and a reflux condenser on the vent gas line at the top of the reactor was charged with a mixture of 0.12 g of cuprous oxide and 1.26 g of 47% hydrogen bromide previously prepared, 0.28 g of N,N'-di-t-butylethylenediamine, 10.22 g of dimethyl-n-butylamine, 2.23 g of di-n-butylamine, 885.9 g of toluene, 47.47 g of 2,6-dimethylphenol, 22.68 g of 2,3,6-trimethylphenol, and 29.86 g of 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane (ADEKA: AO-30). Next, while vigorously stirring, air was started to be introduced into the reactor from the sparger at a rate of 1.05 L / min, and at the same time, a heat medium was passed through the jacket to adjust the polymerization temperature so as to maintain it at 20° C. 200 minutes after the start of air introduction, the air supply was stopped and the inside of the reactor was replaced with nitrogen gas, and then the polymerization mixture was added as an aqueous solution of 1.46 g of ethylenediaminetetraacetic acid tetrasodium salt tetrahydrate (a reagent manufactured by Dojindo Laboratories) and 200 g of water.

[0123] Further, a mixture of 1.0 g of hydroquinone and 40 g of water was added, and the mixture was kept at 20° C. for 1 hour to carry out reduction treatment of the by-product diphenoquinone, and then heated to 70° C. and copper extraction was carried out at 70° C. for 1 hour. Thereafter, the mixture was allowed to stand for separation to separate into an unmodified polyphenylene ether solution (organic phase) and an aqueous phase to which the catalyst metal had been transferred.

[0124] The unmodified polyphenylene ether solution (400 g) was added to a 1-liter jacketed reactor equipped with a line for introducing nitrogen gas at the top of the reactor, stirring turbine blades and baffles, and a reflux condenser at the vent gas line at the top of the reactor. After replacing the inside of the reactor with nitrogen, 27.5 g of triethylamine was added using a syringe while stirring. Then, a mixture of 22.7 g of methacryloyl chloride and 83.6 g of toluene was collected in a syringe and dropped into the system. After the dropwise addition, stirring was continued at room temperature for 3 hours, and then the flask was heated in an oil bath to continue the reaction under reflux. Heating was stopped 2 hours after the start of reflux, and after the temperature returned to room temperature, 2.00 g of methanol was added to stop the reaction. Next, the reaction solution was concentrated until the solid content concentration was 20% by mass, and then washed with ion-exchanged water of the same mass as the concentrated solution. Then, the water layer was removed, and the organic layer was dropped into methanol (5 times the mass of the organic layer) while stirring. Next, the precipitate was filtered, and the filter cake was vacuum dried at 110° C. for 1 hour, to obtain modified polyphenylene ether 1. The resulting modified polyphenylene ether 1 had a number average molecular weight (Mn) of 2,580 g / mol, a weight average molecular weight (Mw) of 5,500 g / mol, and an average number of terminal groups of 3.0.

[0125] <Production of metal clad laminate> <Preparation of varnish> The components of the resin composition, glass cloth, and copper foil were prepared as shown in Table 1. According to the composition shown in Table 2, a heterocyclic compound having an ethylenically unsaturated group, polyphenylene ether, elastomer, crosslinking agent, and other additives were mixed in the parts by mass shown in Table 2 with 82 parts by mass of toluene as a solvent, and stirring was continued until dissolved and / or dispersed. Next, initiators were added to the dissolved materials, and the mixture was thoroughly stirred to obtain a varnish.

[0126] <Preparation of resin-coated copper foil> The obtained varnish was applied onto copper foil so that the film thickness after drying would be 25 μm, and dried in a fan oven at 90° C. for 10 minutes to prepare a resin-coated copper foil. Furthermore, two pieces of the obtained resin-coated copper foil were laminated together so that the resin sides were in contact with each other, and then heated from room temperature at a temperature increase rate of 2°C / min, and then heated to 200°C for 60 minutes under a pressure of 10 kg / cm. 2 A double-sided copper-clad board was produced by vacuum press lamination at 1000 rpm.

[0127] <Preparation of prepreg> A glass cloth substrate was impregnated with the obtained varnish, and then the substrate was passed through a predetermined slit to remove excess varnish, and the substrate was dried for a predetermined time in a drying oven at 120° C. to remove toluene, thereby obtaining a prepreg. The prepreg was then cut to a predetermined size.

[0128] <Preparation of copper-clad laminate> A predetermined number of the obtained prepregs were stacked, and metal foil was placed on both sides of the stacked prepregs, followed by vacuum pressing to obtain a copper-clad laminate. In this vacuum pressing process, the temperature conditions were heating from room temperature at a temperature rise rate of 2°C / min, holding at 200°C for 60 minutes, and applying a pressure of 40 kg / cm. 2 The pressure was applied.

[0129] Evaluation <Identification and analysis of polyphenylene ether> [Number average molecular weight and weight average molecular weight] Gel permeation chromatography (GPC) was used in a chloroform solvent. The number average molecular weight and weight average molecular weight were determined based on a calibration curve using standard polystyrene.

[0130] [Average number of terminal groups] The average number of terminal functional groups per molecule of polyphenylene ether (PPE) was determined by the following method. That is, in accordance with the method described in "Polymers Research Collection, vol. 51, No. 7 (1994), p. 480," a tetramethylammonium hydroxide solution was added to a methylene chloride solution of PPE, and the change in absorbance at a wavelength of 318 nm of the obtained sample was measured with an ultraviolet-visible absorption spectrometer. From this measurement value, the number of phenolic hydroxyl groups before and after the terminal modification of PPE was determined. In addition, the number of molecules of PPE (number average molecular number) was calculated using the number average molecular weight of PPE determined above and the mass of PPE. From these values, the average number of phenolic hydroxyl groups per PPE molecule before and after modification was calculated according to the following formula (1). Average number of phenolic hydroxyl groups per molecule = Number of phenolic hydroxyl groups / number average number of molecules…(1) The average number of functional terminal groups after modification was calculated according to the following formula (2): Average number of terminal functional groups per molecule = Average number of phenolic hydroxyl groups before modification - Average number of phenolic hydroxyl groups after modification ... (2)

[0131] <Glass transition temperature (Tg) of cured resin> The dynamic viscoelasticity of the cured resin was measured, and the glass transition temperature (Tg) was calculated from the temperature at which tan δ was maximum. The measurement was performed using an ARESS (manufactured by TA Instruments) with a test piece length of approximately 45 mm, width of approximately 12.5 mm, and thickness of approximately 3 mm, in twist mode, and at a frequency of 10 rad / s.

[0132] <Metal layer roughness measurement> Ten-point average roughness R of the metal layer surface on the side in contact with the resin layer zjis and the average element length R sm was measured by the following method using a measuring laser microscope (LEXTOLS4100, manufactured by Olympus Corporation) conforming to JIS B0601-2013. (1) Place the measurement sample on the stage with the metal layer surface to be measured facing up. (2) Adjust the focus with a 50x objective lens and take a photograph using [laser observation]. Shooting settings are [Normal], [High Precision], and [Auto]. (3) The measurement area is the imaged 259 μm × 259 μm, and the surface roughness is measured within this area. (4) Select [Surface roughness] and perform [Surface correction] under [Surface pretreatment]. (5) To measure the surface roughness, select [Line roughness] from [Analysis parameters], display horizontal lines at five different locations on the surface image, and calculate the ten-point average roughness R zjis and the average element length R sm Get the numerical value of . (6) Calculate the average of the five values ​​obtained and calculate the ten-point average roughness R zjis and the average element length R sm The method is to measure the ten-point average roughness and element average length R of the metal layer surface. sm get.

[0133] <Static friction coefficient of metal layer surface> The static friction coefficient of the metal layer was measured in accordance with JISP8147:2010. However, the static friction coefficient was measured by using a portable friction meter (Muse Type: 94i-II, manufactured by Shinto Scientific Co., Ltd.) to measure five different random locations on the metal layer surface, and calculating the average value to determine the static friction coefficient.

[0134] <Adhesion between cured resin and metal layer (peel strength)> The stress was measured when the copper foil was peeled off at a constant speed from the double-sided copper-clad board or copper-clad laminate formed by the vacuum press. Specifically, the double-sided copper-clad board or copper-clad laminate was cut into a size of 10 mm wide x 100 mm long. Using an autograph (AG-5000D, manufactured by Shimadzu Corporation), the average load was measured when the copper foil was peeled off from the copper-clad laminate at an angle of 90° at a speed of 50 mm / min, and the average value of three measurements was calculated. The calculated average value was obtained as the peel strength between the resin cured product and the metal layer. The peel strength was ranked according to the following criteria. ◎ (Excellent) 0.45≦Peel strength (N) ○ (Good) 0.4≦Peel strength (N)<0.45 × (bad) Peel strength (N) < 0.4

[0135] <Fine wiring pattern formability> A copper wiring pattern was formed by a subtractive method on the copper-clad laminate formed by the vacuum press, and the formability of the wiring pattern was evaluated. Specifically, first, DF (dry film: Asahi Kasei Sunfort) was laminated onto the copper foil surface of the copper-clad laminate using a roll laminator at a temperature of 110°C, a pressure of 0.4 MPa, and a rotation speed of 1.0 m / min. Then, the laminate was exposed to light through an exposure mask with an L (line) / S (space) of 50 μm / 50 μm at an exposure dose of 100 mJ / cm. 2 Next, a development process was performed by spray etching using an aqueous sodium carbonate solution (developer) to dissolve and remove the areas that were not exposed to light in the exposure process, thereby producing a mask pattern. Next, the copper foil portion not masked by the dry film was etched away using a copper chloride etching solution, and then the DF was peeled off using a sodium hydroxide solution to form a copper wiring pattern. The wiring pattern formability was evaluated by observing the wiring pattern from above with an optical microscope and taking photographs of the top and bottom surfaces of the wiring pattern focused on.

[0136] (Method for evaluating wiring pattern formability) The width of each wiring was measured using photographs taken while focusing on the top and bottom surfaces of the wiring pattern, and the wiring was ranked according to the following criteria. ◎ (Very good): The unevenness of the wiring width on both the top and bottom surfaces (i.e. the difference between the maximum and minimum wiring widths) is 5 μm or less, and the difference in the average wiring widths on the top and bottom surfaces is 10 μm or less. ◯ (Good): Among products with unevenness in the wiring width on both the top and bottom surfaces of 8 μm or less and with a maximum difference in the wiring width between the top and bottom surfaces of 15 μm or less, those that do not meet the criteria of ◎ above. × (defective): Does not meet the above ◎ and 〇 criteria.

[0137] <Insulation reliability in fine wiring patterns (rust prevention / migration resistance)> An inner layer circuit substrate having an electrode wiring pattern of positive and negative electrodes arranged alternately with a wiring width of 100 μm and a wiring interval of 100 μm was produced on the copper-clad laminate obtained above. The resin-coated copper foil or the prepreg and copper foil were laminated on the inner layer circuit substrate, and the temperature was raised from room temperature at a rate of 2°C / min, and the substrate was heated at 200°C for 60 minutes under a pressure condition of 40 kg / cm. 2 After that, a wiring electrode was formed from the inner layer circuit to prepare a sample for migration evaluation. The migration resistance was measured by applying a DC voltage of 50 V under conditions of a temperature of 85°C and a relative humidity of 85%, and observing the change in insulation resistance value and the presence or absence of growth of copper dendrites, and ranking them according to the following criteria. ○ (Good): The insulation resistance value after 500 hours was more than 1×108 Ω and no dendrite growth was observed. △ (Acceptable): Insulation resistance value exceeds 1 x 108 Ω after 500 hours, or no dendrite growth is observed. × (Fail): The insulation resistance value after 500 hours was below 1×108 Ω and dendrite growth was observed.

[0138] <Dielectric constant and dielectric loss tangent> A plurality of prepregs obtained by impregnating a glass cloth with a varnish made of a resin composition were laminated, and the laminate was pressurized by a vacuum press and heat-cured to obtain a cured resin laminate. The dielectric loss tangent at a frequency of 10 GHz was measured by a cavity resonance method. A network analyzer (N5230A, manufactured by Agilent Technologies) and a cavity resonator (Cavity Resornator CP series) manufactured by Kanto Electronics Application Development Co., Ltd. were used as measuring devices. A cured resin laminate with a thickness of about 0.5 mm was cut into a size of about 2 mm wide and 50 mm long so that the warp of the glass cloth of the laminate was the long side. Next, the sample was placed in an oven at 105°C ± 2°C, dried for 2 hours, and then left to stand for 96 ± 5 hours in an environment with a temperature of 23°C and a relative humidity of 50 ± 5%. Thereafter, the relative dielectric constant and dielectric loss tangent of the sample were measured using the above measuring device in an environment with a temperature of 23°C and a relative humidity of 50 ± 5%.

[0139] In addition, for each of the copper foil grades a to e, the difference between the dielectric loss tangent Df1 of Comparative Examples 1 and 2 using a varnish that does not contain a heterocyclic compound having an ethylenically unsaturated group and the dielectric loss tangent Df2 of the Example using a varnish that contains a heterocyclic compound having an ethylenically unsaturated group was calculated, and the results were ranked according to the following criteria. 〇(Good) Df2 - Df1 ≦ 0.0005 △(Acceptable) 0.0005 < Df2 - Df1 ≦ 0.001 ×(Defective) Df2 - Df1 > 0.001

[0140] <Evaluation Results> The copper-clad laminates obtained in the Examples and Comparative Examples were evaluated as described above, and the results are shown in Table 2.

[0141] [Table 1]

[0142] [Table 2]

Claims

1. A metal clad laminate comprising a resin cured product and a metal layer laminated in contact with the resin cured product, the cured resin contains a structural portion derived from a compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms, the cured resin has a relative dielectric constant of 3.3 or less and a dielectric tangent of 0.003 or less, The ten-point average roughness R of the surface of the metal layer that is in contact with the cured resin zjis is 2.0 μm or less, A metal clad laminate, wherein the metal layer has an element average length R sm of 9.0 μm or more on at least one surface.

2. A metal clad laminate comprising a resin cured product and a metal layer laminated in contact with the resin cured product, the cured resin contains a structural portion derived from a compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms, the cured resin has a relative dielectric constant of 3.3 or less and a dielectric tangent of 0.003 or less, The ten-point average roughness R of the surface of the metal layer that is in contact with the cured resin zjis is 2.0 μm or less, The compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms is represented by the following general formula (1): 【Chemistry 1】 In the formula, R 1 represents a hydrogen atom or a monovalent hydrocarbon group, R 2 represents a hydrogen atom, a methyl group, or an ethyl group, and X represents a group represented by the following general formula (X-1): 【Chemistry 2】 (wherein R 3 is a hydrogen atom or a monovalent hydrocarbon group), or the following formula (X-2): 【Chemistry 3】 or the following general formula (X-3): 【Chemistry 4】 (wherein R 4 is a hydrogen atom or a monovalent hydrocarbon group), and Y is a sulfur atom or an NH group.) A metal clad laminate, which is a compound represented by the formula:

3. A metal clad laminate comprising a resin cured product and a metal layer laminated in contact with the resin cured product, the cured resin contains a structural portion derived from a compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms, the cured resin has a relative dielectric constant of 3.3 or less and a dielectric tangent of 0.003 or less, The ten-point average roughness R of the surface of the metal layer that is in contact with the cured resin zjis is 2.0 μm or less, the cured resin contains a structural portion derived from an elastomer, The elastomer is at least one selected from the group consisting of a block copolymer of a vinyl aromatic compound and an olefin-based alkene compound, a hydrogenated product thereof, and a homopolymer of a vinyl aromatic compound; and The metal clad laminate, wherein the content of units derived from the vinyl aromatic compound in the block copolymer or the hydrogenated product thereof is 20 mass % or more.

4. The element average length R of at least one surface of the metal layer sm The metal clad laminate according to claim 2 or 3, wherein the thickness is 5.0 μm or more.

5. The element average length R of at least one surface of the metal layer sm The metal clad laminate according to any one of claims 2 to 4, wherein the thickness is 5.0 µm or more and 100.0 µm or less.

6. The metal clad laminate according to any one of claims 1 and 3 to 5, wherein the compound having a polymerizable group and an aromatic heterocycle having one or more nitrogen atoms has a 1,2,4-triazole structure or a tetrazole structure.

7. the cured resin contains a structural portion derived from an elastomer, The elastomer is at least one selected from the group consisting of a block copolymer of a vinyl aromatic compound and an olefin-based alkene compound, a hydrogenated product thereof, and a homopolymer of a vinyl aromatic compound; and The metal clad laminate according to any one of claims 1, 2, and 4 to 6, wherein the content of units derived from the vinyl aromatic compound in the block copolymer or the hydrogenated product thereof is 20 mass% or more.

8. 8. The metal clad laminate according to claim 1, wherein the static friction coefficient of the surface of the metal layer in contact with the cured resin is 0.38 μs or more and 0.50 μs or less.

9. The metal clad laminate according to any one of claims 1 to 8, wherein the cured resin has a crosslinked structure formed by crosslinking polyphenylene ether having two or more terminal curable functional groups.

10. The metal clad laminate according to claim 9 , wherein the cured resin further has a crosslinked structure formed by crosslinking with a crosslinking agent.

11. The metal clad laminate according to any one of claims 1 to 10, further comprising a glass cloth.

12. A printed wiring board comprising the metal clad laminate according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Easily adhesive resin film

    JP2001298275A

  • Curable polyphenylene ether-based resin composition

    JP2004263099A

  • Resin varnish having low dielectric loss tangent, excellent in stability and circuit board material using the same

    JP2007099893A

  • Prepreg

    JP2017025228A

  • Surface treatment agent, resin composition, and utilization of them

    JP2018016865A